A Study on Native Speakers vs. Non-Native Speakers: Which Make the Best ESOL Teachers? - ALBASIRI, AYMAN THEEB (2017)
As long as ESOL (English for Speakers of Other Languages) is concerned, the misconception that is related to native speakers, or the general prevailing belief that stresses the idea about native English speakers (NES) being the perfect teachers, and that they have the upper hand and that they are far ahead of their non-native speaker’s counterparts. However, numerous studies have revealed that students are not much inclined or pay no significant attention whatsoever to the concept of valuing teachers according to their mother tongue. This study will try to examine and explore the fundamental differences and similarities between native English-speaking teachers (NESTs) and non-native English-speaking teachers (NNESTs) to decide which is better to be employed for teaching English as a Second Language (EFL). Additionally, a comprehensive comparison would be made between the two in terms of pedagogy, language skills, competence and performance. The study will also shed lights on the diversified conceptions and perceptions and insights on both NESTs and NNESTs taking into consideration recent studies and researches so far done in this field. To account for adequate and accurate data that serve this study objectives, an empirical together with a quantitative study design method is used here in order to construct and elicit firm results and conclusions. The anticipated outcomes this study would nearly agree to the simple fact be found out here bringing to light some basic advantages and disadvantages of both NESTs and NNESTs in the field of EFL and the special characteristics they both possess.